ASSESSMENT OF THE STATE OF SMALL AND MEDIUM-SIZED BUSINESSES IN UKRAINE AND THE EU COUNTRIES - Maksymov, Mykhailo (Social Economics, 2024)
The article provides a review of existing research on government policy in the field of support for small and medium enterprises (SMEs) and concludes that the research mainly focuses on descriptive evaluations. Based on this, a proposal has been formulated to apply a data-driven approach to shaping directions and measures for effective SME development support policies. The aim of this study is to substantiate proposals for promoting the development of SMEs based on a comparative analysis of business density and productivity indicators in Ukraine and the EU. The object of the study is the SME sector in Ukraine and the EU, while the subject is the statistical indicators of its performance. The article examines the current state of SMEs, focusing on business density per 10,000 people and the output per employee, comparing these indicators with the EU average and separately with each EU member state.It has been found that as the size of a business increases, the output per employee also rises. From 2011 to 2020, the average business density in Ukraine ranged between 80% and 95% of the EU average but dropped to 67.58% in 2021, reflecting the EU's more effective business support policies post-COVID-19. In 2022, it further declined to 58.18%, demonstrating the negative impact of the Russia-Ukraine war on Ukrainian businesses.The output per employee in Ukrainian businesses is significantly lower than in EU businesses: 2.12 times lower for large businesses, 1.82 times lower for medium-sized businesses, 4.47 times lower for small businesses, and 5.57 times lower for micro-businesses.The volume of goods and services per employee across different sectors of the Ukrainian economy was also analyzed. The most productive sector is J – Information and Telecommunications, while the least productive is E – Water supply; sewerage, waste management, and remediation activities.A policy direction has been proposed to encourage the establishment of new businesses and the transition of existing businesses to higher-productivity sectors, as well as to organize measures to support productivity growth in the least productive sectors.